Iterative thermomechanical processing of alloy 600 for improved resistance to corrosion and stress corrosion cracking. (July 2016) - Telang, Abhishek; Gill, Amrinder S.; Kumar, Mukul; Teysseyre, Sebastien; Qian, Dong; Mannava, Seetha R.; Vasudevan, Vijay K.
Abstract: The effects of thermomechanical processing (TMP) with iterative cycles of 10% cold work and strain annealing, on corrosion and stress corrosion cracking (SCC) behavior of alloy 600 was studied. The associated microstructural and cracking mechanisms were elucidated using transmission (TEM) and scanning electron microscopy (SEM), coupled with precession electron diffraction (PED) and electron back scatter diffraction (EBSD) mapping. TMP resulted in increased fraction of low coincident site lattice (CSL) grain boundaries whilst decreasing the connectivity of random high angle grain boundaries. This disrupted random grain boundary network and large fraction of low CSL boundaries reduced the propensity to sensitization, i.e. carbide precipitation and Cr depletion. After TMP, alloy 600 (GBE) also showed higher intergranular corrosion resistance. Slow strain rate tests in 0.01 M Na2 S4 O6 solution at room temperature show TMP lowered susceptibility to intergranular SCC. To better understand the improvements in corrosion and SCC resistance, orientation maps of regions around cracks were used to analyze the interactions between cracks and various types of grain boundaries and triple junctions (TJs). Detailed analysis showed that cracks were arrested at J1 (1-CSL) and J2 (2-CSL) type of TJs. The probability for crack arrest at special boundaries and TJs, calculated using percolative models, was found to have increased after TMP, which also explains the increase in resistance to corrosion and SCC in GBE alloy 600. A clear correlation and mechanistic understanding relating grain boundary character, sensitization, carbide precipitation and susceptibility to corrosion and stress corrosion cracking was established. Graphical abstract: